Personalized strategies in reproductive medicine for patients with endocrine disorders - O.R. Grigoryan; E.N. Andreeva; I.I. Dedov (Терапевтический архив, 2018)
Endocrine Medical Research center (EMRC) of the Ministry of health of Russia is unique clinical center, that have no analogs in the world. All forms of endocrine disorders may be diagnosed and treated here by implication of innovative methods. Institute of reproductive medicine of EMRC was open on 2017, director of this institute – MD, PhD E.N. Andreeva. Staff of this institute include highly experienced investigators and physicians. One of the most ambitious projects of the institute is development of prevention, diagnostic and treatment algorithm for patients with infertility of endocrine origin. For these purposes large prospective clinical trial (5000 patients) will be conducted with implementation of most modern genetic, laboratory and instrumental diagnostic methods. Results of this trial will allow diagnose, treat and prevent reproductive pathology in patients with endocrine diseases.